Public mental health facility closures and criminal justice contact in Chicago - Muchow, Ashley N. (Criminology & public policy, 2025)
Research summary In 2012, Chicago closed half of its public mental health clinics, which provide services to those in need regardless of their insurance status or ability to pay. Critics of the closures argued that they would result in service shortages and divert untreated patients to the criminal justice system. We explore this claim by examining whether and to what extent the closures increased criminal justice contact. Using a difference-in-differences framework, we compare arrests and mental health transports in block groups located within a half mile of clinics that closed to those equidistant from clinics that remained open. While we find evidence that police-initiated mental health transports increased following the closures, we do not observe similar changes in arrests. Policy implications Chicago's mental health clinic closures remain a contentious issue to this day. Our results suggest that the shuttered clinics were meeting a need that, when left unmet, created conditions for mental health emergencies. While the closures do not appear to have routed untreated patients to the county jail, they increased police contact and, subsequently, transportation to less specialized emergency care facilities. Our findings demonstrate the need to strengthen health care access, crisis prevention, and the mental health safety net to preclude police from acting as mental health responders of last resort.